Optimalisasi Pengelolaan Laboratorium IPA Melalui Workshop Development Management of Laboratory Di SMPN 33 Makassar - Faisal; Hartono; Andi Rahmat Saleh; Sitti Saenab; Hamka L. (Program Studi Manajemen FEB UNM, 2025)
The use of laboratories in science learning plays a crucial role in enhancing students' skills and understanding. However, at UPT SPF SMP Negeri 33 Makassar, the science laboratory has not been utilized optimally. The main inhibiting factor is the lack of understanding among teachers and laboratory assistants in managing and using laboratory equipment. To address this issue, the